Religious Tolerance among Indonesian Islamic University Students: The Pesantren Connection - Thoyib, Muhammad Edy; Degaf, Agwin; Fatah, Anton Abdul; Huda, Miftahul (Journal of Al-Tamaddun, 2024)
This study examines how Pesantren education shapes religious tolerance among students at Islamic universities in Indonesia. Pesantren, traditional Islamic boarding schools, offer a distinct educational experience that emphasizes religious, moral, and social development, setting them apart from formal education. Using a survey of 1,004 students from three Islamic universities in mid-2023, the study investigates key dimensions of religious tolerance through Welch’s t-test. This statistical method was chosen for its ability to handle unequal variances across groups, making it suitable for comparing tolerance levels between Pesantren and non-Pesantren attendees. The analysis reveals that Pesantren attendance significantly enhances interfaith tolerance, particularly in promoting respect for diverse religious practices and fostering open-minded attitudes. These findings highlight the critical role of Pesantren in nurturing tolerant perspectives within Islamic academic environments. The study offers practical recommendations for integrating interfaith dialogue into Islamic education curricula and developing policies that support social cohesion in Indonesia’s diverse society. Furthermore, by applying Social Identity Theory, this research illustrates how religious identity formation within Pesantren contributes to broader social harmony and tolerance. The findings have important implications for educators and policymakers seeking to create more inclusive and tolerant learning environments.